USІNG DІGІTАL TЕCHNОLОGY TО ЕNHАNCЕ SUCCЕSS ІN MАTH CLАSSЕS ОF 11th-GRАDЕ STUDЕNT - Sainova, A. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2023)
The article explores the impact of digital technology on the quality of education in 11th grade mathematics classes. It analyzes the role of information and communication technologies in improving teaching practices and their impact on students. The article stresses the importance of competent use of these technologies and identifies the specifics of digital pedagogy. The study was conducted through an experimental pretest-posttest control group design, and the results suggest that digital technologies will undoubtedly play a significant role in the state's educational process. They will be used in conjunction with traditional forms of education due to their versatile and comprehensive nature, which has a positive effect on all indicators of the quality of education. This approach will help teachers achieve the dynamics, efficiency, and effectiveness of their professional activities.
Keywords: education; digital technology; digital pedagogy; educational process; teaching; math